Alelopatia de espécies arbóreas da caatinga presentes em áreas de diferentes estágios sucessionais - Pontes, Larisse Frota (2018)
Allelopathy can influence the process of ecological succession through the release of chemicals into the environment, which may limit or slow the continuity of succession and influence the composition of the species. Thus, the objective of this work was to investigate how the species-specific relation of allelopathy of the tree species of different successional stages of the caatinga occurs. Laboratory bioassays were performed with aqueous extracts of dehydrated leaves of two species from each successional stage. The species chosen for the initial stage were Mimosa tenuiflora and Cobretum leprosum, for the secondary stage, Anadenanthera colubrina and Libidibia ferrea and late stage, Amburana cearensis and Myracrodruon urundeuva. Different combinations of experiments were done, with test species and target species. The results showed higher allelopathic potential for one of the early species, Mimosa tenuiflora, confirming the different behavior of pioneer tree species. The study concludes that species-specific relationships are as important as environmental conditions, since species considered of the same stage and of different stages have a significant allelopathic effect.